2017
DOI: 10.1038/ncomms15634
|View full text |Cite
|
Sign up to set email alerts
|

High pressure synthesis of a hexagonal close-packed phase of the high-entropy alloy CrMnFeCoNi

Abstract: High-entropy alloys, near-equiatomic solid solutions of five or more elements, represent a new strategy for the design of materials with properties superior to those of conventional alloys. However, their phase space remains constrained, with transition metal high-entropy alloys exhibiting only face- or body-centered cubic structures. Here, we report the high-pressure synthesis of a hexagonal close-packed phase of the prototypical high-entropy alloy CrMnFeCoNi. This martensitic transformation begins at 14 GPa … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
112
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 274 publications
(131 citation statements)
references
References 62 publications
17
112
0
2
Order By: Relevance
“…The chemical interactions in HEAs have been found to follow complex rules with long-ranged interactions causing chemical frustration [11]. This allows the tuning of structures and properties of high-entropy alloys in a manner that is not achievable with conventional alloys and phases [12]. Furthermore, HEAs have been found to be good model systems for investigating fundamental physical interactions, as their properties often fall between those of crystalline and amorphous materials, see e.g.…”
Section: Introductionmentioning
confidence: 99%
“…The chemical interactions in HEAs have been found to follow complex rules with long-ranged interactions causing chemical frustration [11]. This allows the tuning of structures and properties of high-entropy alloys in a manner that is not achievable with conventional alloys and phases [12]. Furthermore, HEAs have been found to be good model systems for investigating fundamental physical interactions, as their properties often fall between those of crystalline and amorphous materials, see e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Compared with temperature, pressure is a more influential controlling parameter in the aspects of decreasing the volume, tuning the packing, and adjusting the energy state. High‐pressure processing of HEAs can obtain accessible phases that cannot be prepared by conventional methods 128. In this part, strain is manifested to have a great impact on the phase structure, including the lattice rearrangement, magnetic moment, and stress concentration 128–130…”
Section: Phase Engineering Of Heasmentioning
confidence: 99%
“…This work, for the first time, achieved the HCP phase in HEAs at ambient conditions, which revealed that pressure could overcome the kinetic barrier between HCP and FCC HEAs. Moreover, Tracy et al took a similar approach to obtain HCP phase of CrMnFeCoNi via a high‐pressure synthesis, and further proposed the mechanism of pressure‐suppressed HEA magnetic moment 128. They found that an HCP phase appeared at 14 GPa and the phase fraction reached a maximum value at 54.1 GPa during the pressure increasing process.…”
Section: Phase Engineering Of Heasmentioning
confidence: 99%
See 1 more Smart Citation
“…[16,187] The polymorphic transition from FCC to HCP was observed in Cantor alloy using in-situ high-pressure synchrotron radiation XRD technique. [188,189] It has been reported that the stable phase of CrMnFeCoNi alloy at low temperatures and high pressures is HCP phase, whereas the FCC phase is stable at higher temperatures and low pressures. The coexistence of FCC and HCP phases occurs in the pressure range of %22 to %41 GPa.…”
Section: Crmnfeconimentioning
confidence: 99%